Dynamic of laser plume from refractory oxide targets; Atomic and molecular pulsed lasers - Evtushenko G. S. Gennady Sergeevich; Lisenkov V. V. Vasily Viktorovich; Osipov V. V. Vladimir Vasiljevich; Platonov V. V.; Podkin A. V.; Spirina A. V.; Tikhonov E. V. Evgeny Vasiljevich; Trigub M. V. Maksim Viktorovich; Fedorov K. V. Kirill Valerjevich (2015, 2015)
В фонде НТБ ТПУ отсутствует